To fly or not to fly: stereotactic MR-guided adaptive radiotherapy effectively treats ultracentral lung tumors with favorable long-term outcomes - Regnery, Sebastian; Katsigiannopulos, Efthimios; Hoegen-Saßmannshausen, Philipp; Weykamp, Fabian; Sandrini, Elisabetta; Held, Thomas; Deng, Maximilian; Eichkorn, Tanja; Buchele, Carolin; Rippke, Carolin; Renkamp, Claudia Katharina; König, Laila; et al. (Lung cancer, 2023)
Background - Stereotactic radiotherapy of ultracentral lung tumors (ULT) is challenging as it may cause overdoses to sensitive mediastinal organs with severe complications. We aimed to describe long-term outcomes after stereotactic magnetic resonance (MR)-guided online adaptive radiotherapy (SMART) as an innovative treatment of ULT. - Patients & methods - We analyzed 36 patients that received SMART to 40 tumors between 02/2020 - 08/2021 inside prospective databases. ULT were defined by planning target volume (PTV) overlap with the proximal bronchial tree or esophagus. We calculated Kaplan Meier estimates for overall survival (OS) and progression-free survival (PFS), and competing risk estimates for the incidence of tumor progression and treatment-related toxicities. ULT patients (N = 16) were compared to non-ULT patients (N = 20). - Results - Baseline characteristics were similar between ULT and non-ULT, but ULT were larger (median PTV: ULT 54.7 cm3, non-ULT 19.2 cm3). Median follow-up was 23.6 months. ULT and non-ULT showed a similar OS (2-years: ULT 67%, non-ULT 60%, p = 0.7) and PFS (2-years: ULT 37%, non-ULT 34%, p = 0.73). Progressions occurred mainly at distant sites (2-year incidence of distant progression: ULT 63%, non-ULT 61%, p = 0.77), while local tumor control was favorable (2-year incidence of local progression: ULT 7%, non-ULT 0%, p = 0.22). Treatment of ULT led to significantly more toxicities ≥ grade (G) 2 (ULT: 9 (56%), non-ULT: 1 (5%), p = 0.002). Most toxicities were moderate (G2). Two ULT patients developed high-grade toxicities: 1) esophagitis G3 and bronchial bleeding G4 after VEGF treatment, 2) bronchial bleeding G3. Estimated incidence of high-grade toxicities was 19% (3-48%) in ULT, and no treatment-related death occurred. - Conclusion - Our small series supports SMART as potentially effective treatment of ULT. SMART with careful fractionation could reduce severe complications, but treatment of ULT remains a high-risk procedure and needs careful benefit-risk-assessment.